Bacterial diversity, quantitative risk assessment of spring waterborne pathogens and their biocontrol through phyto-biosorbents - Aysha Aziz; Saiqa Andleeb; Nuzhat Shafi; Wajid Arhsad Abbasi; Aisha Nazir (PLoS ONE, 2026)
Bacterial contamination of drinking water is a significant cause of water-borne illnesses in many developing countries, where water sources are commonly shared by the community. Therefore, the recent research was designed to screen the bacterial diversity associated with spring water, to assess the bacterial risk in both adults and children, and to remediate bacterial contaminants using green remediation technology via Brassica rapa and Spinacia oleracea . Microbial growth media, microscopic techniques, biochemical tests, ribotyping, antibiogram, and resistogram analysis were used to characterize bacterial isolates. The bactericidal effect of extracts of phytoabsorbents was evaluated against spring water-associated bacteria through the agar well diffusion method. The ex-situ remediation via phytoabsorbents was done to decontaminate spring water. Bacillus amyloliquefaciens , Bacillus subtilis, Bacillus cereus , Bacillus anthracis, Lysinibacillus fusiformis , Bacillus wiedmannii , uncultured Bacillus sp. , Bacillus weihenstephanensis , and Bacillus thuringiensis were characterized through the Maximum Likelihood method and Tamura-Nei model. The highest mean risk of illness (%) due to Bacillus species was recorded in children (56.67% to 70.0% compared to the adults (47.0% to 50.0%). All isolated spring water-associated bacteria were resistant to amoxycillin, aztreonam, tobramycin, tazobactam, ceftriaxone, and cefuroxime sodium. Similarly, all spring water-associated bacteria showed resistance against lead, cadmium, and chromium. The root extract of B. rapa and S. oleracea showed the maximum zone of inhibition of spring water-associated bacteria (10.0 ± 0.0 mm to 19.0 ± 0.0 mm) compared to the seeds and aerial parts extracts. Ex-situ remediation findings illustrated that both plants efficiently declined the microbial load, did not affect the sprouting and growth of B. rapa compared to the S. oleracea, and could be used as biosorbent to decontaminate spring water.